'Americanism not globalism will be our credo!': An analysis of the economic nationalism(s) of Trump's administration and an agenda for further research. Issue 3 (23rd February 2021) - Baltz, Matthew J.
Abstract: Donald Trump has often been labelled an 'economic nationalist'. But what does this mean, and what does his administration's economic nationalism look like in practice? This article argues that 'economic nationalism' remains too broad a category to be useful for analysis but can be salvaged if economic nationalists are distinguished by their relationships to the state, namely, by the primary ends to which they seek to use state power and by the organizations of the state they target to achieve those ends. Doing so results in a typology dividing economic nationalism into four variants: militarist, developmental, liberal and populist. Applying this typology to an analysis of Donald Trump's presidency reveals an administration dominated by economic nationalism's populist, liberal and militarist variants. The article concludes by outlining an agenda for future research on the subject.